2004
DOI: 10.1104/pp.104.039677
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Auxin-Conjugate Hydrolases That Contributes to Free Indole-3-Acetic Acid Levels during Arabidopsis Germination

Abstract: Auxins are hormones important for numerous processes throughout plant growth and development. Plants use several mechanisms to regulate levels of the auxin indole-3-acetic acid (IAA), including the formation and hydrolysis of amide-linked conjugates that act as storage or inactivation forms of the hormone. Certain members of an Arabidopsis amidohydrolase family hydrolyze these conjugates to free IAA in vitro. We examined amidohydrolase gene expression using northern and promoterb-glucuronidase analyses and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
201
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(219 citation statements)
references
References 54 publications
10
201
3
5
Order By: Relevance
“…Hypocotyl elongation and cotyledon cell expansion also depend on auxin. The triple hydrolase mutant, which has decreased free IAA levels in whole seedlings (Rampey et al, 2004), displays reduced hypocotyl lengths when grown in the light at 22°C but not at 28°C ( Fig. 6A; Rampey et al, 2004), suggesting that conjugates provide some of auxin that drives hypocotyl elongation at normal growth temperatures.…”
Section: Defects In Iaa Conjugate Hydrolases Results In Shortened Rootmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypocotyl elongation and cotyledon cell expansion also depend on auxin. The triple hydrolase mutant, which has decreased free IAA levels in whole seedlings (Rampey et al, 2004), displays reduced hypocotyl lengths when grown in the light at 22°C but not at 28°C ( Fig. 6A; Rampey et al, 2004), suggesting that conjugates provide some of auxin that drives hypocotyl elongation at normal growth temperatures.…”
Section: Defects In Iaa Conjugate Hydrolases Results In Shortened Rootmentioning
confidence: 99%
“…The triple hydrolase mutant, which has decreased free IAA levels in whole seedlings (Rampey et al, 2004), displays reduced hypocotyl lengths when grown in the light at 22°C but not at 28°C ( Fig. 6A; Rampey et al, 2004), suggesting that conjugates provide some of auxin that drives hypocotyl elongation at normal growth temperatures. When we examined ibr1 ibr3 ibr10 for a similar phenotype, we found that 8-d-old ibr1 ibr3 ibr10 seedlings displayed wild-type hypocotyl lengths at both temperatures (Fig.…”
Section: Defects In Iaa Conjugate Hydrolases Results In Shortened Rootmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In contrast, formation of IAA-aspartate and IAA-glutamate marks auxin for subsequent metabolic degradation and conjugation of IAA with either alanine or leucine maintains a ready pool for formation of the active free acid form of auxin. 15,16 Thus, metabolism of IAA and JA provides a simple means of modulating plant hormone receptor occupancy and controlling gene responses. Some GH3 family of proteins catalyze the conjugations of various amino acids to plant hormones, including JA and IAA; however, Characterization of multiple group II GH3 genes in Arabidopsis also demonstrates critical roles in plant growth and development primarily through the conjugation of IAA to amino acids.…”
Section: Modulating Plant Hormones By Enzyme Actionmentioning
confidence: 99%